(untitled) (Iranian Journal of Kidney Diseases, 2012)
After the first description of Kaposi sarcoma in 1872, many cases of this tumor were reported worldwide. This tumor is multifocal and laryngeal involvement is considered to be as unusual site. Kaposi sarcoma is almost always are associated with classical skin lesion, and only about 5% of non-acquired immune deficiency syndrome Kaposi sarcomas are reported to be located in the larynx. We report a kidney transplant recipient diagnosed with solitary laryngeal Kaposi sarcoma 21 months after transplantation, who was treated with combined surgery, chemotherapy, and immunosuppressive modification.